Analysis of Linguistic Development in the Arab World and the West - Achmad, Syauqi Amirudin; Rofi, Moh ’Affan; Fikri, Muhamad Yusuf (Proceedings of International Conference on Islamic Civilization and Humanities, 2025)
This study aims to analyze the development of linguistic science in both the Arab world and the West, with a focus on the theories and contributions of linguistic scholars as found in literary studies. The results show that linguistic studies in the West cover a broader range of topics from social, political, and intellectual perspectives. In contrast, linguistic studies in the Arab world tend to be more narrowly focused, particularly on the study of the Qur’an and Hadith. As a result, linguistic development in the Arab world has experienced stagnation, while in the West it has seen significant progress.